2016
DOI: 10.3928/01477447-20151222-18
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Cruciate Ligament Reconstruction in the United States: A Nationwide Database Study From 1998 to 2010

Abstract: This study evaluated inpatient cruciate ligament reconstruction in the United States during a 13-year period. The Nationwide Inpatient Sample database was used to identify inpatient cruciate ligament reconstructions performed from 1998 to 2010. National trends in incidence, patient demographics, perioperative complications, length of stay, and total admission costs were evaluated. The impact of various contributing factors on these outcomes was further evaluated using multivariable regression analyses. The rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…ACLR performed in outpatient ambulatory surgery centres has been beneficial in several aspects, including higher patient satisfaction[ 22 ] and cost reduction[ 23 ] compared to patients operated on an inpatient setting. Moreover, Lyman et al[ 8 ] reported that rates of readmission within ninety days were significantly higher among patients who had undergone an inpatient ACLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACLR performed in outpatient ambulatory surgery centres has been beneficial in several aspects, including higher patient satisfaction[ 22 ] and cost reduction[ 23 ] compared to patients operated on an inpatient setting. Moreover, Lyman et al[ 8 ] reported that rates of readmission within ninety days were significantly higher among patients who had undergone an inpatient ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that also evaluated this parameter found a similar result. Scillia et al[ 23 ] evaluated only inpatient reconstructions in the US from 1998 to 2010 and reported that the mean length of stay was 1.6 days during the study period. The authors also identified a significant increase in total admission costs per case.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo que avaliou a taxa de readmissão após a RLCA demonstrou que pacientes com mais de 40 anos foram readmitidos com mais frequência do que pacientes mais jovens, independentemente de outros fatores. (8) As cirurgias realizadas em caráter ambulatorial são benéficas em muitos aspectos, como a redução de custos (35) e a maior satisfação do paciente (36) comparado com o paciente operado em caráter hospitalar. Além disso, um estudo americano relatou que as taxas de readmissão hospitalar dentro de 90 dias após a RLCA foi significativamente maior entre pacientes que operaram em caráter hospitalar.…”
Section: Discussionunclassified
“…Estudo realizado nos Estados Unidos, avaliando apenas as reconstruções realizadas em regime hospitalar de 1998 a 2010, relatou que o tempo médio de internação foi 1,6 dias. (35) Outro estudo similar, porém com dados do sistema de saúde pública do Brasil, encontrou um tempo médio de internação de 1,8 dias em 2014. (41) Nesse mesmo estudo, os autores mostraram uma redução no tempo de internação ao longo dos anos.…”
Section: Discussionunclassified
See 1 more Smart Citation